2009
DOI: 10.3181/0807-rm-230
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Hydrogen Sulfide Regulates Pulmonary Artery Collagen Remodeling in Rats with High Pulmonary Blood Flow

Abstract: The mechanisms responsible for the structural remodeling of pulmonary vasculature induced by increased pulmonary blood flow are not fully understood. This study explores the effect of endogenous hydrogen sulfide (H2S), a novel gasotransmitter, on collagen remodeling of the pulmonary artery in rats with high pulmonary blood flow. Thirty-two Sprague-Dawley rats were randomly divided into sham, shunt, sham+PPG (D,L-propargylglycine, an inhibitor of cystathionine-gamma-lyase), and shunt+PPG groups. After 4 weeks o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 28 publications
2
14
0
Order By: Relevance
“…Our results revealed for the first time that H 2 S also markedly prevents the development of cardiac fibrosis, decreasing the collagen content in the cardiac tissue, yet the detailed signaling pathway mechanism was not yet elucidated. Li et al (27) reported that H 2 S may reduce collagen accumulation in the pulmonary artery through increasing its degradation by regulating matrix metalloproteinase (MMPs) and metalloproteinase (TIMPs) activities. This needs to be confirmed in future studies on hypertrophied ventricle.…”
Section: Discussionmentioning
confidence: 99%
“…Our results revealed for the first time that H 2 S also markedly prevents the development of cardiac fibrosis, decreasing the collagen content in the cardiac tissue, yet the detailed signaling pathway mechanism was not yet elucidated. Li et al (27) reported that H 2 S may reduce collagen accumulation in the pulmonary artery through increasing its degradation by regulating matrix metalloproteinase (MMPs) and metalloproteinase (TIMPs) activities. This needs to be confirmed in future studies on hypertrophied ventricle.…”
Section: Discussionmentioning
confidence: 99%
“…MMP-9 activity was suppressed in CBS−/+ mice treated with NaHS (Figure 3). Others have suggested that endogenous H 2 S may decrease the level of MMP-13 and TIMP-1 in rats (Li et al, 2009). The increased MMP-2,-9 protein, mRNA levels and MMP-9 activity caused degradation of matrix proteins and increased BBB permeability.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, endogenous H 2 S prevented pulmonary collagen remodeling induced by high pulmonary blood flow (Li et al, 2009). In addition, downregulation of the endogenous H 2 S pathway in lungs was shown to induce structural remodeling of pulmonary vasculature (Xiaohui et al, 2005).…”
Section: S and Lung Remodeling In Hibernationmentioning
confidence: 99%